2008
DOI: 10.1080/10942910701611170
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proximate, Fatty Acid and Amino Acid Compositions of Various Types of Fish Roes

Abstract: Proximate compositions, amino acid compositions and fatty acid compositions of fish roe have been measured and compared. Glutamic acid, aspartic acid, lysine, and serine have been the major amino acids. However, Imperial-type caviar has also included higher amounts of tryptophan (p < 0.05). Essential /Nonessential (E/NE) ratio has been found to be between 0.93-1.23, and n3/n6 ratio has been found to be 2.56-8.06. Major fatty acids were C16:0, C18:1 n9c, C16:1 n7, C20:5n3, and C22:6 n3. Fish roes contain high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 18 publications
6
43
2
2
Order By: Relevance
“…The proximate composition of the beluga roe, both cultivated and wild, were within the range reported for sturgeon roe by other researchers (Table 1) [25,26]. However the fatty acid profile of the cultivated and wild sturgeon roes was different and it is likely that the reduced levels of polyunsaturated fatty acids negatively affected fertilization ratio in the cultivated beluga sturgeon.…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rsupporting
confidence: 51%
See 3 more Smart Citations
“…The proximate composition of the beluga roe, both cultivated and wild, were within the range reported for sturgeon roe by other researchers (Table 1) [25,26]. However the fatty acid profile of the cultivated and wild sturgeon roes was different and it is likely that the reduced levels of polyunsaturated fatty acids negatively affected fertilization ratio in the cultivated beluga sturgeon.…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rsupporting
confidence: 51%
“…The results of fatty acid profiles in current study showed significant differences between wild and domestic beluga roes (Table 1) Turan [26] reported that palmitic acid was the most abundant SAFA in beluga caviar compare to other sturgeons caviar. While there is no available data comparing cultivated beluga and wild roe.…”
Section: Fatty Acid Profile Chemical Composition and Fertilization Rmentioning
confidence: 88%
See 2 more Smart Citations
“…Cantoni, Bianchi, Renon, and Beretta (1975) stated that salmon roes showed high protein contents, and this composition suits particularly for human and animal consumption, and this statement was also corroborated by Bledsoe et al (2003). Fish roes offer quality protein with high biological value and are a rich source of glutamic acid, lysine, serine, and aspartic acid (Bledsoe et al, 2003;Mol & Turam, 2008). According to Moriya et al (2007), salmon roes contain significantly more docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) than tuna and sardine oils.…”
Section: Resultsmentioning
confidence: 85%